The Effectiveness of G-Suite Docs on the Students’ Writing Skills at SMA Negeri 1 Batuan - Norani Yanuar Subandi; J. Priyanto Widodo; Shierly Novalita Yappi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The primary goal of this study was to determine the effectiveness of G-Suite Docs on students’ writing skills as well as students’ perceptions of its implementation at SMA Negeri 1 Batuan. It was carried out on the 40 students in the eleventh grade, who were divided into two groups: control and experiment groups, using an experimental design. The results showed that Ha was accepted and Ho was rejected, indicating that the writing method using G-Suite Docs has a significant effect on improving students’ writing ability and could be used effectively in writing class. The students’ perceptions then demonstrated that using G-suite docs had a significant impact on their writing ability, and they enjoyed writing using the G-suite docs method. It was proven by the Cronbach’s Alpha (α) statistical test, with the limitation of a variable being said to be reliable if the Cronbach's Alpha value is > 0.5 and can be said to be reliable.